Actualization of Checks and Balances between Executive, Legislative and Judicial in Indonesia - Deddy Supriady Bratakusumah (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
The study analyzes the implementation of the democratic model and the government system in Indonesia. Checks and Balances among democracy pillars is the main focus of the analysis. The important finding of the study is that democracy in Indonesia does not have consistency in term of the system.